Sistem Informasi Penjualan Dan Persediaan Barang Dengan Metode Fifo Berbasis Multiuser Pada Toko Cat Jaya Gemilang Semarang - Lida Hartatik; Arsito Ari Kuncoro; Kasih Purwantini (Switch : Jurnal Sains dan Teknologi Informasi, 2023)
In the era of rapid technological and information system developments that encourage people, both groups and individuals, both government and private institutions to utilize technological developments have a very important role in the progress of human life. Rapid technological developments One of the advantages of computers in processing data can increase effectiveness, productivity, and efficiency in carrying out work in current technology makes it easier to manage inventory. Cash sales transactions are said to have been carried out if the company has received payment from the customer and will then be handed over by the company to the customer of the Cat Jaya Gemilang Semarang shop, a company engaged in the field of building paint trading in Semarang. Currently, the system that is running is still manual, namely the administration section records incoming and outgoing goods, all recorded in the book for sales are also recorded manually. With manual recording, books are easily damaged or torn, data in the warehouse records is sometimes not the same as the physical goods that exist, and there is no data security. With the above problems, the author created a system that can reduce weaknesses by creating a systematic application in the database.